Curriculum Transformation in Quranic Learning: From Tabarak to Utrujah Method - Ammalia Tulili; Muhammad Fazis; Nurlaila Nurlaila (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study investigates the transformation of Qur’anic learning curriculum from the traditional Tabarak method to the innovative Utrujah method, highlighting the urgency of pedagogical renewal in Islamic education. The research aims to analyze the rationale for curriculum change, the process of implementation, and its implications for learners’ engagement and comprehension. Employing a qualitative case study approach, data were collected through classroom observation, in-depth interviews with teachers, and curriculum document analysis. Data analysis followed descriptive qualitative procedures, including reduction, presentation, and conclusion drawing. The framework of change management applied in this study refers to Kurt Lewin’s three stages: unfreezing, changing, and refreezing. Findings reveal that during the unfreezing stage, internal evaluation identified limitations of the Tabarak method, such as weak reading skills, reliance on audio, and absence of quality control mechanisms, which fostered collective awareness of the need for change. The changing stage was characterized by the implementation of the Utrujah method through strengthening tahsin before tahfiz, grouping students by ability, enhancing teacher roles, intensive mentoring, and continuous monitoring, accompanied by adaptation dynamics and initial resistance. In the refreezing stage, transformation was stabilized through standardized SOPs, sustained supervision, teacher accountability, and improved student achievements. The study concludes that the Utrujah method offers a model of Qur’anic education modernization that remains relevant to contemporary needs while preserving sacred tradition.